Parental Responsibolity, Young Children and Healthcare Law - Bridgeman, Joanna (Cambridge University Press, 2013)
Being a parent brings with it manifold social, moral and legal responsibilities in relation to the physical, emotional and intellectual growth and development of the child as well as his or her safety, security, happiness and well-being.